2020
DOI: 10.1111/1556-4029.14478
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two New Methods for DNA Extraction of “Legal High” Plant Species

Abstract: A quick, simple, and high‐yield nucleic acid isolation process is crucial for high‐quality DNA analysis. The ability of the MicroGEM PDQeX phytoGEM system and Omega Bio‐tek E.Z.N.A.® Plant DS Mini kit to extract PCR‐ready DNA was evaluated by extracting the forensically relevant “legal high” plant species: Ipomoea purpurea, Artemisia absinthium, Mitragyna speciosa, Datura stramonium, and Papaver somniferum. The plant material was pulverized, processed using the manufacturer’s plant protocol for the PDQeX Nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…They also concluded that the QIA-GEN DNeasy kit is not a preferred method when dealing with large numbers of samples due to the long time that is required to complete the isolation. Our initial MicroGEM DNA concentration results were similar to previous research such as described by Ryan et al [39], which showed a very low recovered DNA concentration (less than 3 ng/µl) when using MIGROGEM on different plant tissues. After optimisation, we substantially increased the concentration to over 15 ng/µl and up to 78 ng/µl using MicroGEM.…”
Section: Discussionsupporting
confidence: 90%
“…They also concluded that the QIA-GEN DNeasy kit is not a preferred method when dealing with large numbers of samples due to the long time that is required to complete the isolation. Our initial MicroGEM DNA concentration results were similar to previous research such as described by Ryan et al [39], which showed a very low recovered DNA concentration (less than 3 ng/µl) when using MIGROGEM on different plant tissues. After optimisation, we substantially increased the concentration to over 15 ng/µl and up to 78 ng/µl using MicroGEM.…”
Section: Discussionsupporting
confidence: 90%
“…Sinensis). At present, some studies have reported various of novel methods of medicinal plants identi cation, such as barcode-based melting curve analysis, DNA labeling or 1 HNMR metabolite ngerprinting and so on 26,27 . Although these methods can accurately identify species, they require specialized knowledge, statistical analysis, and complex instruments.…”
Section: Discussionmentioning
confidence: 99%
“…The extracted DNA was quanti ed using A260/280 ratio by QuickDrop™ Spectrophotometer, and all the values were greater than 1.80. To evaluate the sensitivity of the LAMP method, we diluted MO genomic DNA by a 10-fold dilution method, with a concentration range of 1 × 10 − 3 pg/µl to 1 × 10 3 pg/µl 26 . According to the commonly used genes encoding ITS, ITS2, psbA-trnH, matK, and rbcl published by GenBank, we selected the ITS2 gene sequence (No: AB715224.1) as the target gene for the primer sequence after referenced articles and used Blast analysis in NCBI (http://www.ncbi.nlm.nih.gov/BLAST).…”
Section: Herbal Sample Collection and Dna Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…2019 GC-MS analysis of fifty samples of medicinal herbs collected from herb shops located in different parts of Iran [ 286 ]; overview of over 400 performance and image enhancing drugs confiscated in Italy in the period 2017–2019 [ 287 ]; evaluation of DNA extracted from the forensically relevant “legal high” plant species: Ipomoea purpurea, Artemisia absinthium, Mitragyna speciosa, Datura stramonium, and Papaver somniferum [ 288 ]; 2020 review of the types of drugs that may be illegally added in health food according to their pharmacological activities, advances in detection technologies for illegal drugs and future development prospects [ 289 ]; 2021 review of the significance of medicinal plants in forensic investigations to detect criminal offenses [ 290 ]; review of toxicological aspects and analytical methods for twelve plant specimens (Areca catechu, Argyreia nervosa, Ayahuasca, Catha edulis, Datura stramonium, Lophophora williamsii, Mandragora officinarum, Mitragyna speciosa, Piper methysticum Forst, Psilocybe, Salvia divinorum and Tabernanthe iboga) [ 291 ].…”
Section: Routine and Improved Analyses Of Abused Substancesmentioning
confidence: 99%